1996
DOI: 10.1056/nejm199609123351104
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Impairment in Children Exposed to Polychlorinated Biphenyls in Utero

Abstract: In utero exposure to polychlorinated biphenyls in concentrations slightly higher than those in the general population can have a long-term impact on intellectual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
554
6
8

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,046 publications
(593 citation statements)
references
References 21 publications
25
554
6
8
Order By: Relevance
“…Similar effects have previously been reported for certain coplanar and ortho-substituted PCBs (Eriksson and Fredriksson 1996a, 1996bEriksson et al 1991). In addition, effects of prenatal and postnatal exposure to PCBs, such as lower gestational age and birth weight (Fein et al 1984;Rylander et al 2000;Taylor et al 1984), delayed development (Guo et al 1994), and intellectual impairment (Jacobson and Jacobson 1996), have been reported in humans.…”
supporting
confidence: 81%
“…Similar effects have previously been reported for certain coplanar and ortho-substituted PCBs (Eriksson and Fredriksson 1996a, 1996bEriksson et al 1991). In addition, effects of prenatal and postnatal exposure to PCBs, such as lower gestational age and birth weight (Fein et al 1984;Rylander et al 2000;Taylor et al 1984), delayed development (Guo et al 1994), and intellectual impairment (Jacobson and Jacobson 1996), have been reported in humans.…”
supporting
confidence: 81%
“…In Taiwan, pregnant mothers were accidentally exposed to PCBs through the ingestion of contaminated rice oil and neurodevelopmental abnormalities were observed in their offspring (Chen et al 1992). Children born to mothers who ingested PCBcontaminated fish also exhibited neurological impairment (Jacobson and Jacobson 1996). This evidence confirmed the long-term impact of PCBs on cognitive deficits and intellectual dysfunction.…”
Section: Rotating Rod Testmentioning
confidence: 65%
“…Produced in the United States until 1977 (Laden et al, 1999 ), PCBs are highly resistant to degradation, persist in animal and environmental reservoirs, and ascend the food chain, depositing in human tissues. Research suggests that PCB exposure in utero or during infancy is associated with lowered birth weight and gestational age Taylor et al, 1984 ), intellectual impairment (Jacobson and Jacobson, 1996 ), and delayed development (Guo et al, 1994 ) .…”
Section: Introductionmentioning
confidence: 99%